An Analytical and Numerical Approach for Shear Failure of Pier-Wall Connections in Typical Dutch URM Buildings. Issue 1 (2nd January 2023) - Fusco, Daniela; Addessi, D.; Messali, F.; Rots, J. G.; Pampanin, S.
ABSTRACT: Since the 1980s, calcium silicate element masonry has been commonly used in Dutch buildings, and vertical continuous joints have been usually located at the corner of perpendicular walls. Since the shear failure of these joints may significantly reduce the seismic performance of the flanged wall and therefore of the entire building, the assumption of rigid connection may be inaccurate, unlike for the traditional interlocking of bricks in running bond textures. In this paper, analytical and numerical approaches to study the failure of vertical joints in the seismic assessment of URM buildings are presented. The first part of the work focuses on two different numerical models to study the nonlinear behaviour of the vertical connection; the related critical numerical issues are then discussed. The second part introduces an analytical method able to estimate the lateral force–displacement curve of a flanged wall, which considers the possible failure of the connection. In particular, the method is derived from the section analysis approach developed for controlled rocking deformable systems. The comparison between the numerical simulations and the analytical method proves the capacity of the latter to provide a quick but sufficiently accurate estimate of the force–displacement curve of a URM U-Shaped wall.